PENGEMBANGAN KURIKULUM BERBASISKAN KEWIRAUSAHAAN DI PERGURUAN TINGGI KEISLAMAN SWASTA (PTKIS) - SUBANDI, SUBANDI (Universitas Islam Negeri Raden Intan Lampung, 2015)
Asian nations will face MEA (Masyarakat Ekonomi ASEAN) in the 21st century. Every nation must prepare itself. The most important will be prepared is human resource. However, it will find problems, if the nations do not prepare themselves well. That problem is if they do not change human resource, they will be customer in their country. As education place, private institutes have way to solve the problems. They must give the students with knowledge about entrepreneurship. So, needed the curriculum based on entrepreneurship. This study discusses about developing curriculum based on entrepreneurship to prepare human resource. The design of this study is a qualitative research. The collecting data was done by applying observation and interview method. In observation method, the researcher observed about how the implementation of curriculum based on entrepreneurship to prepare human resource is. In interview method, the researcher asked about developing curriculum based on entrepreneurship to prepare human resource. The researcher also used the documentation method to get more information. To answer the research problem, the researcher used descriptive analysis to explain data analysis. The result from the developing curriculum based on entrepreneurship to prepare human resource is the students have generic life skill from that curriculum and the students have religion value in entrepreneurship. The implementation of curriculum based on entrepreneurship can connect affective, cognitive and psychomotoric skill so the students will be entrepreneur and they can develop their soft skill and hard skill. It will